Respons Pertumbuhan dan Produksi Tanaman Selada (Lactuca sativa L.) Terhadap Pemberian Pupuk Organik Cair Urin Kambing Pada Beberapa Jarak Tanam - Immanuel Hans Alexander Surbakti; Ratna Rosanti Lahay; T Irmansyah (Universitas Sumatera Utara, 2016)
This research was carried out on land the area residents,pasar 1 street No.89 Tanjung Sari, Medan at altitude of ± 25 asl from May 2015 through July 2015, using factorial randomized block design with two treatment factors, namely liquid organic fertilizer goat urine with treatments of 0, 200, 400, 600 cc/ L of water and Plant Spacing with treatment 20x20 cm, 25x20 cm and 30x20 cm. Parameters measured were plant height, number of leaves, fresh weight total per sample, selling fresh weight per sample, fresh weight of roots per sample, harvest index and shoot-root ratio.The results showed that the liquid organic fertilizer goat urine application had no significant effect on all parameters. Plant spacing significantly affected parameters plant height, number of leaves, fresh weight total per sample, selling fresh weight per sample, and fresh weight of roots per sample. Interaction of liquid organic fertilizer goat urine and spacing of treatment had no significant effect on all parameters of existing observations. Keywords: lettuce, liquid organic fertilizer goat urine, plant spacing